2009
DOI: 10.1177/1750481308098764
|View full text |Cite
|
Sign up to set email alerts
|

Television news, narrative conventions and national imagination

Abstract: AND KEYWORDSAbstract: By and large, contemporary news stories are stories about a particular nation, told to an audience that is seen and addressed in national terms. However, the understanding of the exact ways in which national imagination becomes engrained in the narrative conventions of news reporting is still rather limited, in particular when it comes to audiovisual genres. This article aims to fill a part of this blank by examining the links between national imagination and the narrative conventions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Moreover, this framing appears so routine and normal to suggest that this ‘Team Arab’ approach is typical of the way that all sport is reported (Mihelj et al. : 70). Therefore, though the event may not be everyday itself, the discourse used appears typical of al‐Jazeera 's framing of events to inculcate a sense of Arab identity (Downey and Koenig : 70–1).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, this framing appears so routine and normal to suggest that this ‘Team Arab’ approach is typical of the way that all sport is reported (Mihelj et al. : 70). Therefore, though the event may not be everyday itself, the discourse used appears typical of al‐Jazeera 's framing of events to inculcate a sense of Arab identity (Downey and Koenig : 70–1).…”
Section: Methodsmentioning
confidence: 98%
“…However, at the same time, as an international event and institution it is predictable, structured and ‘normal’ and how media bodies such as al‐Jazeera report it (Dayan and Katz : 1–10) differs greatly from its coverage of conflict and crisis that have dominated the literature on new Arabism (Mihelj et al. : 70). Although all media are spun to reflect a certain editorial line, coverage of conflict and political news is done so more overtly than everyday items such as sport (Herman and Chomsky : 1–14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many media scholars have observed that Al‐Jazeera's broadcasts have contributed to a sense of unity among Arab communities (Fahmy & Johnson, ; Mihelj, Bajt, & Pankov, ; Miladi, ; Phillips, ; Pintak, ; Rinnawi, ). In fact, some scholars (Pintak, ; Rinnawi, ) note that during the recent uprisings in Arab communities, Al‐Jazeera presented a slanted viewpoint in its approach to the events' unfolding.…”
mentioning
confidence: 99%
“…The presence of war is among the key contextual factors that can account for rapid changes in media discourse, including a shift from 'banal' to 'hot' forms of nationalism (Mihelj et al 2009a). During periods of conflict, the usual democratic mechanisms regulating the production and circulation of public information are weakened, and the media are drawn into the promotion of social relations and values preferred by the ruling political structure (Van Dijk 2006: 15).…”
Section: Introductionmentioning
confidence: 99%